Current Topics in Pharmacological Research on Bone Metabolism: Molecular Basis of Ectopic Bone Formation Induced by Mechanical Stress - Ken-Ichi Furukawa (Elsevier, 2006)
Abstract.: Ectopic bone formation (EBF) is frequently found in various tissues and affects the prognosis of diseases accompanied by EBF. Although the mechanism of EBF remains unclear, several local factors that influence the progression of EBF have been proposed. We have been focusing on the role of mechanical stress as a local factor in EBF in spinal ligament tissues, that is, ossification of the posterior longitudinal ligament (OPLL), which causes serious neurological deficiencies. Transcriptome analyses revealed that the expressions of several marker genes related to bone remodeling were enhanced after exposure of ligament cells derived from OPLL patients (OPLL cells) to cyclic stretching as a type of mechanical stress. However, no significant alterations in gene expressions were detected after cyclic stretching of ligament cells derived from non-OPLL patients. OPLL cells exposed to cyclic stretching released several autocrine/paracrine factors that are known to mediate bone remodeling. These results suggest that OPLL cells have been transformed into cells that are highly sensitive to mechanical stress, which may induce the progression of OPLL. These observations provide information regarding the role of mechanical stress in the process of EBF. Keywords:: spinal ligament, ectopic bone formation, mechanical stress, microarray, transcriptome analysis